ENRICHING CLASSROOMS WITH TECHNOLOGY: EFFECTIVENESS OF ICT INTEGRATION IN TEACHING AGRICULTURAL SCIENCE IN SENIOR SECONDARY SCHOOLS IN BENUE STATE - GBEYONGU FREDERICK TERKIMBI; AKAA CHARITY WANGER; ONU DEBORAH OGBENE (International Studies Journal)
Information and Communication Technologies (ICTs) have become part of individual lives in the 21st century. ICT is often employed to improve the quality of instructional delivery to help in equipping the students with relevant skills and knowledge. This paper stressed on the integration of ICT tools in teaching Agricultural Science in Senior Secondary Schools in Benue State. The paper dealt with the impact of ICT tools in teaching Agricultural Science. Examined the usage level of ICT tools by learners, determined the effect of ICT integration on student’s attitude/interest and challenges of integrating ICT in Agricultural Science classes. Descriptive survey research design was adopted for the study with the population of 6250 and a sample size of 120 respondents. The instrument for data collection was a questionnaire validated by three experts; data was collected by the researcher and analyzed using mean and standard deviation while chi square was used to test the null hypotheses at .05 level of confidence. Findings revealed amongst others that ICT devises if used in Agricultural Science instruction in teaching learning process, will boost learner’s performances, makes learning more interesting and enhances student’s retention abilities. Teachers attest that, teacher’s incompetency of ICT use, lack of teachers’ self-confidence, traditional appraisal of ICT and lack of ICT mainstreaming into schools’ policy were some of the constraints faced. Therefore, for effective integration of ICT in teaching Agricultural Science in secondary schools, it was recommended that teachers of Agricultural Science should be trained periodically; sufficient ICT facilities should be provided; there should be constant power supply; internet services should be enhanced, among others.